ATSAR DA'WAH OF TABLIG CONGREGATION ON THE SOUTH COAST OF GORONTALO CITY: ATSAR DA'WAH OF TABLIG CONGREGATION ON THE SOUTH COAST OF GORONTALO CITY - Kango, Andries; Suryani, Wahidah (Farabi, 2020)
This study specifically focuses on elaborating on the atsar (impact) of the da'wah activities conducted by the Tablighi Jamaat in the South Coast region of Gorontalo City. Furthermore, based on the findings, good da'wah practices in coastal areas will be identified. The scope of da'wah atsar in this context refers to how the mad'u (audience of da'wah) responds to the Tablighi Jamaat's da'wah efforts in the region. These responses encompass cognitive, affective, and behavioural aspects. The objective of this study is to identify the atsar and good da'wah practices applicable to coastal areas. Accordingly, this research aims to: (1) Describe the da'wah activities of the Tablighi Jamaat in the South Coast region of Gorontalo City, and (2) Conduct a deeper analysis of the da'wah footprint of the Tablighi Jamaat in the region. The findings of this study indicate that: First, the da'wah method employed by the Tablighi Jamaat follows the  khuruj method, which involves venturing out in the path of Allah. This process begins with fostering social connections (silaturahmi), reciting ta'lim , and subsequently engaging in jaula practices. This approach has been implemented along the southern coast of Gorontalo City for the past 12 years. Second, the atsar of the Tablighi Jamaat's da'wah efforts in the South Coast region is significant and yields optimal results. This is evidenced by observable transformations in the community’s daily life, such as the increased observance of prayer, enhanced religious knowledge, strengthened social ties, and active participation in the commemoration of Islamic holidays.